Distribution network topology identification method based on state estimation with mixed integer programming and structural equation model - Liu, Bo; Chen, Jiaxuan; Li, Jiang (International journal of electrical power & energy systems, 2024)
Compared with the existing methods, the current-based identification method proposed in this paper ensures high identification accuracy at a lower observation level, and its main contributions are summarized as follows:•Topology identification can be performed with limited node measurements using SEM to improve the dynamic topology identification accuracy.•The introduction of auxiliary variables relaxes the constraints, solves the problem of intersection of feasible regions, and improves the solvability of the algorithm.•Reprogramming the operation mode constraints and equivalently relaxing the quadratic terms in them reduces the computational complexity while improving the identification accuracy. Distribution network topology identification (DNTI) is an important prerequisite for distribution system operation. Frequent topology changes and limited measurement equipment make identifying the correct topology unavoidably challenging. To this end, this paper proposes a state estimation method for distribution network topology identification using a small amount of phasor measurement unit (PMU) measurement data. Firstly, this paper introduces the application of the structural equation model (SEM) in distribution networks and explains the relationship between branch currents and topology. Then, auxiliary variables are introduced for the feasible domain problem present in the algorithm, which improves the solvability of the algorithm. In addition, this paper reconsiders the operation mode constraints in terms of nodes from the perspective of distribution network operation mode. The Structural Equation Modeling-based Mixed Integer Programming (SEM-MIP) method proposed in this paper can be solved using existing commercial solvers, and its effectiveness has been verified by simulation in IEEE 33-node test system and IEEE 123-node test system.